Visual word recognition of Chinese–Japanese bilinguals: limited role of phonology - Jiao, Zhongyan; Du, Leyi; Wang, Yifan; Li, Yixian (Frontiers in Psychology, 2024)
In visual word identification, the effects of orthography and phonology on lexical semantic access have been a hot psycholinguistic topic. Previous masked translation priming studies on alphabetic scripts have shown that in bilingual lexical recognition, phonological similarity plays a facilitating role. However, whether cross-language phonological similarity would also facilitate target processing for bilinguals if neither of their two languages is alphabetic has not been clearly established. The present study using a lexical decision task, tested Chinese-Japanese bilinguals using Chinese-Japanese cognate translation pairs. Primes and targets are either phonologically similar cognates or phonologically dissimilar cognates. Event-related potential (ERP) data showed no differences between the phonologically similar and dissimilar contexts within the 90-170 ms and 170-270 ms time windows. Within the 350-500 ms time window, they showed significance, and the phonologically dissimilar condition elicited a larger negative wave. These results are inconsistent with the conclusions of studies based on alphabetic scripts, revealing that in the processing of logographic scripts, the activation time of phonology and semantics is the same, and the role of phonology is limited.